Belgian photographers 1839-1939 : a chronological bibliography of publications from 1945 to 2020, with an author and a photographer index - Driesen, Frank, 1954- (Turnhout : Brepols, 2021)
Searching for information on locally, nationally or internationally renowned amateur or professional photographers working in Belgium before the Second World War? Maybe you will find some information on the internet, but still a lot has only been published in print. This printed information is very scattered and difficult to find. It may have been published in journals on culture and art, on heritage, on local and general history, on photography and history of photography, in catalogues of collections and exhibitions, in reference works, monographs and theses. 'Belgian Photographers 1839-1939' provides an overview of printed publications published after 1945 about Belgian photographers active from the discovery of photography until the Second World War. It presents a chronological bibliography, an author index and-most importantly- a completely comprehensive photographer index. This means that the references of all publications in which a particular photographer is mentioned, can be found in the bibliography. Definitely this book will be an essential guide for all those with an interest in the history of photography in Belgium, including photo and art historians, heritage researchers, genealogists and archivists.